2022
DOI: 10.3390/biom12030344
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Human-Induced Pluripotent Stem Cell-Derived Astrocytes in Neurodegenerative Disorders

Abstract: Most neurodegenerative disorders have complex and still unresolved pathology characterized by progressive neuronal damage and death. Astrocytes, the most-abundant non-neuronal cell population in the central nervous system, play a vital role in these processes. They are involved in various functions in the brain, such as the regulation of synapse formation, neuroinflammation, and lactate and glutamate levels. The development of human-induced pluripotent stem cells (iPSCs) reformed the research in neurodegenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 140 publications
0
14
0
Order By: Relevance
“…As an alternative to using NSC/NPC, it is possible to appropriately differentiated stromal/stem cells isolated from other environment alone (i.e., MSC) or in combination with NSC [ 83 ], induced pluripotent stem cells (iPSC) derived from an appropriate somatic cell [ 84 , 85 , 86 , 87 ], or extracellular vesicles (EV) derived from MSC or a relevant cell cultured under optimal in vitro culture conditions [ 88 , 89 ]. The latter are becoming an important avenue of research as they are not immunogenetic, can contain a range of molecules that can enhance endogenous cell repair of the damaged tissue, and could therefore be used in non-autologous application, which would overcome potential limitations associated with autologous materials.…”
Section: Limitations Regarding Use Of Brain-associated Nscmentioning
confidence: 99%
“…As an alternative to using NSC/NPC, it is possible to appropriately differentiated stromal/stem cells isolated from other environment alone (i.e., MSC) or in combination with NSC [ 83 ], induced pluripotent stem cells (iPSC) derived from an appropriate somatic cell [ 84 , 85 , 86 , 87 ], or extracellular vesicles (EV) derived from MSC or a relevant cell cultured under optimal in vitro culture conditions [ 88 , 89 ]. The latter are becoming an important avenue of research as they are not immunogenetic, can contain a range of molecules that can enhance endogenous cell repair of the damaged tissue, and could therefore be used in non-autologous application, which would overcome potential limitations associated with autologous materials.…”
Section: Limitations Regarding Use Of Brain-associated Nscmentioning
confidence: 99%
“…iPSCs were first discovered by Takahashi and Yamanaka in 2006 from adult somatic cells via integrating four factors (Sox2, Oct3/4, Klf4, and cMyc) [ 118 ]. Till date, with the great capacity of self-renewal and differentiation into all somatic cell types, iPSC-based cell therapy has been widely investigated, and their potential in the treatment of neurodegenerative diseases has been studied [ 119 , 120 ]. Rajasingh et al have compared human iPSC-derived MSCs (iMSCs) and MSCs and found that iMSCs still maintained MSC characteristics without any chromosomal abnormalities even at later passages, while MSCs started to lose their characteristics at that time, indicating that iMSCs might be an alternative cell type to MSCs for the treatment of various diseases [ 121 ].…”
Section: Exosomes-based Therapy and Application In Cerebral I/r Injurymentioning
confidence: 99%
“…Several possible human-like model systems have been described. Firstly, the development of human induced pluripotent stem cell (iPSC) technologies has transformed research into neurodegenerative diseases, allowing the generation of specific neural cell types from patients and healthy donors to model human disease (Kumar et al, 2022). Human iPSCs have been successfully differentiated into astrocytes and extensively studied (Kumar et al, 2022;Ren & Dunaevsky, 2021), however this approach is not without limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the development of human induced pluripotent stem cell (iPSC) technologies has transformed research into neurodegenerative diseases, allowing the generation of specific neural cell types from patients and healthy donors to model human disease (Kumar et al, 2022). Human iPSCs have been successfully differentiated into astrocytes and extensively studied (Kumar et al, 2022;Ren & Dunaevsky, 2021), however this approach is not without limitations. Protocols for generating human iPSC-derived astrocytes vary considerably, and are continuously being improved, with no single protocol having been widely accepted as the "gold standard" (Kumar et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation